A 3-year retrospective study of 866 children and adolescent outpatients followed in the Nice Pediatric Psychotrauma Center created after the 2016 mass terror attack - Gindt, Morgane; Fernandez, Arnaud; Zeghari, Radia; Ménard, Marie-Line; Nachon, Ophelie; Richez, Aurélien; Auby, Philippe; Battista, Michele; Askenazy, Florence (Frontiers in Psychiatry, 2022)
Background: The mass terrorist attack in Nice, France in July 2016 caused deaths and injuries in a local population, including children and adolescents. The Nice Pediatric Psychotrauma Center (NPPC) was opened to provide mental health care to the pediatric population (0-18 years) who experienced traumatic events. Objectives: This study describes the specificity of the care pathway for young trauma victims, with an explanation of how the NPPC works during the first three years.